Fatigue life estimation of 1-D aluminum beam using electromechanical impedance technique - Lim, Yee Yan (2012)
A comprehensive structural health monitoring (SHM) system is essential for damage detection, characterization and prognosis. The recent advent of smart materials, such as the electro-mechanical impedance (EMI) technique, employing the piezo-impedance transducers as collocated actuators and sensors, is known for its ability in damage detection and characterization.